Clinical features and prognostic factors in small bowel tumors: A retrospective evaluation of eighty cases (Annals of Medical Research, 2021)
Aim: Small bowel tumors are rare tumors originating from the gastrointestinal tract. In this study, we aimed to determine the clinical characteristics and prognostic factors effecting survival in patients with small bowel cancer. Material and Methods: Eighty patients with small bowel malignancy between February 2002 and December 2016 were evaluated retrospectively. Clinical characteristics, pathological features, laboratory results, progression-free and overall survival rates were determined. The effect of the evaluated parameters on survival was examined.Results: The incidence of small bowel tumors was 0.36% in patients admitted to our clinic. The median age of the patients was 55 and 68.8% of the patients were male. The most common histologic subtype was adenocancer (42.5%), and the most common localization site (37.5%) was duodenum. 27 of patients (33.8%) had metastasis at the time of diagnosis. The most common site of metastasis was liver. Overall survival rate was 59.1% in the third year and 52.9% in the fifth year. The median disease-free survival (DFS) rate was 78% in the third year and 68% in the fifth year. Conclusion: Information about these tumors is limited in the literature and was presented in retrospective case series. In our study, the most common localization site was found as duodenum and the most common histological type was adenocancer. Prognosis of patients undergoing curative surgical resection was found to be better.
Keywords: Small bowel tumors; prognostic factors; adenocancer